VARIED METHODS CAN INCREASE STUDENT'S LEARNING ACHIEVEMENT IN LESSONS THEMES IN CLASS II ELEMENTARY SCHOOL 004STUDY YEAR IV KOTO STUDY 2019/2020 - Sri Palupi (STKIP Rokania Pasir Pangaraian, 2021)
This study aims to improve student achievement in thematic lessons by using various methods. The approach used in this research is a qualitative and qualitative approach with an action research design. The research design is arranged in a cycle that is recycled including: planning, implementing, monitoring, reflecting. The results of studies and direct observations at the Pendalian IV Public Elementary School 004 Koto still use the lecture method in learning. Based on the data from the assessment results obtained by students from the first cycle to the second cycle, it can be seen that the score obtained by each student increased. And the results of the study indicate that the use of varied methods in thematic learning can improve the learning outcomes of grade II students at SD Negeri 004 Pendalian IV Koto.